Accuracy of robotic computer-assisted implant surgery in clinical studies: a systematic review and meta-analysis - Zixin Luo; An Li; Alexey Unkovskiy; Jiang Li; Florian Beuer; Zhe Wu; Ping Li (BMC Oral Health)
Abstract Objectives To analyze the accuracy of the robotic system in clinical studies and assess potential factors that might affect the accuracy of robotic implant placement. Materials and methods PubMed, Embase, and Cochrane Central Register of Controlled Trials were used to search for studies published from August 2014 till October 2024. Studies on robotic computer-assisted implant surgery (R-CAIS) were identified. Furthermore, manual searches were performed for selected journals. Only clinical studies were included. Subgroup analysis was performed based on robot autonomy, different dentitions, and the working principle of the camera. Results Sixteen studies met the inclusion criteria, evaluating 908 implants. The meta-analysis of accuracy showed that the average global platform deviation, global apex deviation, and angular deviation were 0.69 mm (95% CI: 0.61‒0.77, I 2 = 94%), 0.72 mm (95% CI: 0.64‒0.79, I 2 = 93%), and 1.62° (95% CI: 1.34°‒1.89°, I 2 = 96%), respectively. In subgroup analysis, Meta-generic inverse variance analysis observed statistically significant differences in global platform deviation and apex deviation between robots using infrared and mechanical tracking (p < 0.01), as well as between those using visible light and mechanical tracking (p < 0.01). No significant differences were observed between autonomous and semi-active systems and different dentitions. Conclusion The R-CAIS technology demonstrated a high level of accuracy. However, further large-scale, multi-center, randomized, controlled clinical trials are necessary to compare robotic implant placement with other techniques, and the additional factors influencing robotic implant placement must be explored.